Nuclear pore protein NUP88 activates anaphase-promoting complex to promote aneuploidy - Naylor, Ryan M.; Jeganathan, Karthik B.; Cao, Xiuqi; van Deursen, Jan M. (The Journal of Clinical Investigation, 2016)
The nuclear pore complex protein NUP88 is frequently elevated in aggressive human cancers and correlates with reduced patient survival; however, it is unclear whether and how NUP88 overexpression drives tumorigenesis. Here, we show that mice overexpressing NUP88 are cancer prone and form intestinal tumors. To determine whether overexpression of NUP88 drives tumorigenesis, we engineered transgenic mice with doxycycline-inducible expression of Nup88. Surprisingly, NUP88 overexpression did not alter global nuclear transport, but was a potent inducer of aneuploidy and chromosomal instability. We determined that NUP88 and the nuclear transport factors NUP98 and RAE1 comprise a regulatory network that inhibits premitotic activity of the anaphase-promoting complex/cyclosome (APC/C). When overexpressed, NUP88 sequesters NUP98-RAE1 away from APC/CCDH1, triggering proteolysis of polo-like kinase 1 (PLK1), a tumor suppressor and multitasking mitotic kinase. Premitotic destruction of PLK1 disrupts centrosome separation, causing mitotic spindle asymmetry, merotelic microtubule-kinetochore attachments, lagging chromosomes, and aneuploidy. These effects were replicated by PLK1 insufficiency, indicating that PLK1 is responsible for the mitotic defects associated with NUP88 overexpression. These findings demonstrate that the NUP88-NUP98-RAE1-APC/CCDH1 axis contributes to aneuploidy and suggest that it may be deregulated in the initiating stages of a broad spectrum of human cancers.